1995
DOI: 10.1172/jci117925
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral size in elderly women with osteoporosis. Mechanical implications and relationship to fractures.

Abstract: Reductions in bone density are a major determinant of vertebral fractures in the elderly population. However, women have a greater incidence of fractures than men, although their spinal bone densities are comparable. Recent observations indicate that women have 20-25% smaller vertebrae than men after accounting for differences in body size. To assess whether elderly women with vertebral fractures have smaller vertebrae than women who do not experience fractures, we reviewed 1,061 computed tomography bone densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(74 citation statements)
references
References 29 publications
(38 reference statements)
1
67
0
6
Order By: Relevance
“…Thus, results of the present study agree with previous reports that suggest a feed-forward pattern for erector spinae and multifidus activation relative to deltoid onset [3,17,21,23,47]. A major element of the present study is that EMG recordings were made at commonly fractured sites, and from the paraspinal muscles, which are known to contribute significantly to compressive vertebral loading due to their short moment arm, particularly in individuals with vertebral fractures [13]. Although EMG was not collected from participantspecific fracture levels, the majority of fractures sustained by participants in this study occurred at T6, in agreement with previous reports [7,11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, results of the present study agree with previous reports that suggest a feed-forward pattern for erector spinae and multifidus activation relative to deltoid onset [3,17,21,23,47]. A major element of the present study is that EMG recordings were made at commonly fractured sites, and from the paraspinal muscles, which are known to contribute significantly to compressive vertebral loading due to their short moment arm, particularly in individuals with vertebral fractures [13]. Although EMG was not collected from participantspecific fracture levels, the majority of fractures sustained by participants in this study occurred at T6, in agreement with previous reports [7,11].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that factors other than BMD may influence the aetiology of first-time and subsequent vertebral fracture [4]. Local factors such as cortical bone structure [33], bone quality [1] and bone geometry [13] appear to have an influential role. However, extraosseous factors may also influence vertebral fracture aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture-induced changes in vertebral morphology causing greater flexion moments locally and in adjacent vertebral levels may perpetuate morphologic changes and increase subsequent fracture risk. Contributions of vertebral geometry [24], densitometry [4] and bone quality characteristics [1,41] in individuals with fractures are also likely to account for some of this increased risk. Shear forces were greater at the level of fracture and one level above, while compression forces were greater at one level below in the fracture compared to equivalent level mean forces of the non-fracture group.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in body height between the allelic variants, indicating an influence of the TNF-a 2 863 polymorphism on bone size. Previous studies (8,31,32) have emphasized the importance of bone size as a determinant of bone strength. Further supporting the role of TNF-a in determining bone size, is the observed independent correlation of TNF-a plasma levels to lumbar spine area.…”
Section: Discussionmentioning
confidence: 99%
“…It is not only mineral density of the skeleton that is important for bone strength. Bone size is a significant determinant for fractures of the vertebral bodies, as Gilsanz et al (8) have shown. Even small changes in size, particularly in external diameter, have a major effect on mechanical properties of a bone (9).…”
Section: Introductionmentioning
confidence: 96%